Role of private sector for HRH (Human Resource for Health) production in Nepal - Dixit, Hemang (Journal of Kathmandu Medical College, 2014)
Human Resource for Health production was started in Nepal in a limited way some eighty years ago and picked up a somewhat faster pace from the 1950s as per the requirements at that time. The establishment of the Institute of Medicine led to some diversification but it was only after 1990 that there has been a much larger involvement of the private sector in the production of Human Resources for Health. Although a number of categories have been listed in this article, the position of doctors, dentists and nurses has been dealt with in more detail. The information provided from relevant councils and some non-governmental organisations regarding the numbers produced and working in Nepal has been quoted. Not much information is available regarding the Nepalis working out of the country. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10634Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, page: 97-103